Table for upside down practices - Gala, Vânia (Repertório, 2023)
[Title Erased] [Name author Erased] Abstract In this paper I describe the collective performance entitled [Titleerased] [reference erased]. The performance was part of the programme [“”], an event on black feminisms. The particular performance(s) performed at [author+title erased] are in this sense rehearsals of the particular positioning of upside down and a web of other various positionings and performances that emerged under this context. The performance assumed the performative conversational form in a long table with the participants. Departing from the idea of positioning as performative or even more mundanely as a position assumed in, with or within black bodies the conversational performance framed questions and speculated about particular positionings. In this regard, the performative table echoes Glissant’s (2010) sensibility in a belief that things, concepts, ideas do not necessarily follow a transparent deductive course but are often the product of intuitively complex networks in relation. In other respects, these performance(s) reflect a relevant aspect of dance practice. As a praxis – without forgetting its highly oral facet – dance is characterized by “a radical hospitality” towards unfamiliar “languages, unknown processes without evident protocols or contracts” [erased] and in many respects opaque. Opaque to the body, the performers and other various intervenients under choreographic performative processes or trainings.